Alizarin-graphene nanocomposite for calibration-free and online pH monitoring of microbial fuel cell. (January 2022) - Ma, Yaohong; Xiao, Leilei; Wei, Yunwei; Kumar, P. Senthil; Tan, Yang; Li, Yiwei; Zang, Hengchang
Abstract: Microbial fuel cells (MFCs) are sensitive to acidity variations in both bioelectricity generation and biochemical digestion aspects, therefore online pH monitoring is of necessity to guarantee optimal function of MFCs. Present pH meters hardly fulfill this special need. In this work, we designed a novel voltammetric pH sensor based on electrochemically reduced graphene oxide (rGO) modified screen printed electrode. By surface doping of alizarin, good linearity of pH sensing over the range of 4.0–9.0 can be realized. Fast readout can be acquired within 15 s for each test. pH monitoring for artificial wastewater with inoculum of granular activated sludge in a MFC was successfully illustrated. Specially, it was verified that the performance was improved with alizarin doping due to the enhanced rGO surface proton diffusion. This approach provides an online, calibration-free and long stable pH monitoring method for the future MFC development. Graphical abstract: Image 1 Highlights: Graphene oxide (GO) interface realized all-solid-state voltammetric pH quantification. Nernstain response of GO enhanced by surface doping of alizarin reaching pH range over 4.0–9.0. Stable pH quantification was illustrated for 7 continuous days. Calibration-free and stable pH monitoring for MFC was realized.